A sodium iron sulfate material and its preparation method and application

By forming a highly stable amorphous phase cladding layer on the surface of sodium ferric sulfate material, the problem of sodium ferric sulfate being sensitive to air is solved, and its air stability and electrochemical properties are significantly improved, achieving long-term stability and efficient electrochemical performance of the material.

CN119208581BActive Publication Date: 2025-03-07SHENZHEN INST OF ADVANCED TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411720003.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-07
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

As the cathode material of sodium ion battery, sodium ferric sulfate has problems of air sensitivity, resulting in the formation of residual alkali and trivalent iron impurities on the surface, increasing the difficulty of pulping and coating, and deteriorating specific capacity and circulation performance.

Method used

By performing rapid heat treatment in a protective gas atmosphere, a highly stable amorphous phase coating layer is formed to isolate the contact between the crystalline phase of the sodium ferric sulfate and air, and improve the air stability and electrochemical properties of the material.

Benefits of technology

The good air stability and excellent electrochemical performance of sodium ferrous sulfate material are achieved. After being able to stand in the air for 12 months, the electrochemical performance has no significant decline, which significantly improves the material's magnification and circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208581B_ABST
    Figure CN119208581B_ABST
Patent Text Reader

Abstract

The present invention relates to a sodium iron sulfate material and a preparation method and application thereof, belonging to the field of energy storage technology. The sodium iron sulfate material provided by the present invention comprises a sodium iron sulfate crystalline phase, and at least a portion of the surface of the sodium iron sulfate crystalline phase is coated with a sodium iron sulfate amorphous phase. The present invention coats at least a portion of the surface of the sodium iron sulfate crystalline phase with a highly stable sodium iron sulfate amorphous phase, effectively isolating the contact between the internal sodium iron sulfate crystalline phase particles and the air, and improving the air stability of the sodium iron sulfate material; and the amorphous amorphous phase provides abundant vacancy defects, making metal migration easier than in the crystalline phase, thereby promoting electrode kinetics. The sodium iron sulfate material provided by the present invention has good air stability, rate performance and long cycle performance. The material can be left in the air for a long time, and the electrochemical performance after being left for 12 months has no obvious decline. The material can be used to prepare a high-performance sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to a sodium iron sulfate material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries face problems such as uneven distribution of lithium resources, uncontrollable costs, insufficient safety, and poor low-temperature performance. Compared with lithium-ion batteries, sodium-ion batteries have many advantages. The crustal reserves of sodium resources are abundant (2.75%), which is more than 400 times that of lithium (0.0065%), and they are evenly distributed around the world and easy to extract. In addition, sodium-ion batteries have higher internal resistance than lithium-ion batteries, less instantaneous heat generation in the case of short circuit, lower temperature rise, and higher thermal runaway temperature than lithium-ion batteries, which have higher safety; sodium-ion batteries have a wider operating temperature range (−40°C to 80°C), which is suitable for extremely cold and hot scenes such as northern and southern my country; sodium-ion batteries have excellent fast charging capabilities, and charging time only takes about 10 minutes; sodium-ion batteries can use lower-cost aluminum foil as positive and negative current collectors, further reducing battery costs. Therefore, as a supplement to lithium-ion batteries, sodium-ion batteries are expected to occupy a certain market in low-speed electric vehicles, communication base stations, large-scale energy storage, and other fields. Therefore, it is of great significance to develop efficient and low-cost sodium-ion battery technology.

[0003] As a key component of sodium-ion batteries, positive electrode materials largely determine key parameters of sodium-ion batteries such as cost, energy density, and cycle life. The sodium storage capacity of positive electrode materials and the patency of transmission channels determine the energy density and power density of sodium-ion batteries. At the same time, the stability and impurity composition of positive electrode materials will affect the life of the battery. At present, the mainstream sodium-ion positive electrode materials are divided into three categories: oxides, polyanionic compounds, and Prussian blue analogs. In comparison, oxide positive electrode materials have a simple structure, high energy density, and moderate cycle performance; polyanionic positive electrode materials have a stable structure, low energy density, and the best cycle performance; Prussian blue analogs have an adjustable working voltage, good rate performance, and the cycle performance needs to be improved.

[0004] Sodium ferric sulfate (chemical formula Na 2+x Fe 2-y (SO4)3, x=0~0.7, y=0~0.35) has attracted extensive attention from researchers due to its advantages of abundant crustal reserves of raw materials, low cost, high working voltage and good long cycle performance. It is considered to be a potential positive electrode material for sodium ion batteries. However, this material is sensitive to humidity and oxidizing atmosphere. If it is exposed to air for a long time, it will be affected by water vapor and oxygen in the air, forming surface residual alkali, trivalent iron impurities and even phase transformation, which will increase the difficulty of material pulping and coating, increase irreversible capacity loss, and seriously deteriorate the cycle performance.

[0005] Therefore, one of the key problems of sodium iron sulfate is its sensitivity to air. Due to the interaction with moisture and oxygen in the air, sodium iron sulfate will have residual alkali on the surface, and some ferrous ions will be oxidized, which increases the difficulty of pulping and coating, and deteriorates the specific capacity and cycle performance. To address this problem, a study prepared a nitrogen-doped graphene-coated sodium iron sulfate positive electrode, which improved the material's antioxidant capacity. After being exposed to air for one month, the Fe 3+ The content (14%) is significantly lower than that of the uncoated material (29%); there are also studies reporting reduced graphene oxide coated sodium iron sulfate positive electrode, but it does not provide the material's environmental stability; and there is a study that provides a hydrophobic and lipophilic sodium iron sulfate protected by oleic acid and vaseline, showing improved humidity stability. However, most of the existing studies require the use of graphene materials, which are expensive; and the preparation of hydrophobic and lipophilic sodium iron sulfate requires repeated ball milling three times, which is a complicated process; and most of the materials obtained still contain trivalent iron, which is not conducive to the performance of electrochemical performance. Summary of the invention

[0006] The present invention aims to solve one of the above technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a sodium iron sulfate material, which has easy-to-obtain raw materials, low cost, simple preparation process, and good air stability, rate and cycle performance.

[0007] A second object of the present invention is to provide a method for preparing the sodium ferric sulfate material.

[0008] A third object of the present invention is to provide a sodium iron sulfate positive electrode material.

[0009] A fourth object of the present invention is to provide a sodium ion battery.

[0010] A fifth object of the present invention is to provide an application of a sodium ion battery.

[0011] In order to achieve the above object, the technical solution adopted by the present invention is:

[0012] A first aspect of the present invention provides a sodium iron sulfate material, comprising a sodium iron sulfate crystalline phase, wherein at least a portion of the surface of the sodium iron sulfate crystalline phase is coated with a sodium iron sulfate amorphous phase.

[0013] The sodium iron sulfate material according to the first aspect of the present invention has at least the following beneficial effects:

[0014] In the present invention, at least part of the surface of the sodium ferric sulfate crystalline phase is coated with a highly stable sodium ferric sulfate amorphous phase. On the one hand, the amorphous phase wraps the sodium ferric sulfate crystalline particles inside, which is conducive to isolating the sodium ferric sulfate from contact with the air, protecting the sodium ferric sulfate, and achieving the purpose of improving the air stability of the sodium ferric sulfate; on the other hand, the amorphous phase provides abundant vacancy defects, which makes metal migration (such as Na + ) becomes easier than in the crystalline phase, thereby promoting electrode kinetics. The conversion reaction can be introduced by virtue of the inherent defects in the amorphous structure, and the amorphous phase characteristics make the material less susceptible to potential structural disorders associated with repeated conversion / reconversion reactions, resulting in a sodium iron sulfate material with stable performance.

[0015] In some embodiments of the present invention, the sodium iron sulfate amorphous phase is formed by heat treating the sodium iron sulfate crystalline phase.

[0016] The sodium iron sulfate crystalline phase in the present invention can form the surface-coated sodium iron sulfate amorphous phase after heat treatment, without adding additional inactive raw materials to form a coating layer, the preparation process is simple, and the obtained sodium iron sulfate material has good air stability and excellent electrochemical performance.

[0017] A second aspect of the present invention provides a method for preparing a sodium iron sulfate material, comprising the following steps:

[0018] S1, heating the sodium iron sulfate crystals to a temperature T under a first protective gas atmosphere and a pressure P, and keeping the temperature for a time t, then stopping the heating to obtain a heat-treated sample;

[0019] S2, maintaining the pressure at P, introducing a second protective gas at a flow rate v, cooling the heat-treated sample, and obtaining the sodium iron sulfate material after cooling;

[0020] Among them, the pressure P ranges from 0.1 to 1000 MPa; the temperature T ranges from 350 to 3000°C; the time t ranges from 0.1 to 15 s; the flow rate v ranges from 50 to 2000 mL / min; and the first protective gas is the same as or different from the second protective gas.

[0021] The method for preparing the sodium iron sulfate material according to the second aspect of the present invention has at least the following beneficial effects:

[0022] The present invention conducts rapid heat treatment on sodium ferric sulfate crystals in an atmosphere of protective gas by heat treatment under specific conditions, rapidly heats up in a very short time to form an ultrafast thermal shock effect, and then rapidly cools and quenches to complete the amorphous transformation on the surface of the grains. This highly stable amorphous package isolates the contact between the internal sodium ferric sulfate particles and the air, and effectively improves the air stability of the sodium ferric sulfate material. In addition, heat treatment under high temperature conditions promotes the structural reorganization of the sodium ferric sulfate material, reduces the original defects, and further improves the structure and electrochemical properties of the sodium ferric sulfate material. The preparation method provided by the present invention has simple preparation steps, low energy consumption, and good uniformity and high yield of the obtained product. The sodium ferric sulfate material obtained by the method has good air stability, rate performance and long cycle performance. The material can be left in the air for a long time, and the electrochemical performance after being left for 12 months has no obvious decline.

[0023] In some embodiments of the present invention, the first protective gas includes an inert gas, a reducing gas or a combination thereof; and / or the second protective gas includes an inert gas, a reducing gas or a combination thereof.

[0024] In some embodiments of the present invention, the first protective gas includes at least one of nitrogen, argon, helium, sulfur dioxide, hydrogen or hydrogen sulfide; and / or the second protective gas includes at least one of nitrogen, argon, helium, sulfur dioxide, hydrogen or hydrogen sulfide.

[0025] In some embodiments of the present invention, the chemical formula of the sodium iron sulfate crystals is Na 2+x Fe 2-y (SO4)3, x=0~0.7, y=0~0.35.

[0026] In some embodiments of the present invention, the raw materials for preparing the sodium iron sulfate crystals include an iron source, a sodium source and a sulfur source.

[0027] In some embodiments of the present invention, the iron source includes at least one of ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous sulfate, ammonium ferrous sulfate, ammonium ferric sulfate, ferric nitrate, ferrous chloride, ferric chloride or ammonium ferric citrate.

[0028] In some embodiments of the present invention, the sodium source includes at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium citrate or sodium hydroxide.

[0029] In some embodiments of the present invention, the sulfur source includes at least one of ferrous sulfate, ferric sulfate, ammonium ferrous sulfate, ammonium ferric sulfate, sodium sulfate, sodium bisulfate, potassium sulfate or ammonium sulfate.

[0030] The third aspect of the present invention provides a sodium ferric sulfate positive electrode material, wherein the raw materials for preparing the sodium ferric sulfate positive electrode material include the sodium ferric sulfate material described in the first aspect of the present invention, or the sodium ferric sulfate material prepared by the preparation method described in the second aspect of the present invention.

[0031] The sodium iron sulfate positive electrode material according to the third aspect of the present invention has at least the following beneficial effects:

[0032] The sodium ferric sulfate of the first aspect of the present invention and the sodium ferric sulfate material prepared by the preparation method of the second aspect of the present invention have good air stability and can be stably placed in an air environment for 12 months without obvious attenuation of electrochemical performance; the sodium ferric sulfate material is made into a positive electrode material to obtain good electrochemical performance.

[0033] The fourth aspect of the present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material, an electrolyte and a separator; the positive electrode material is selected from the sodium iron sulfate positive electrode material described in the third aspect of the present invention.

[0034] The sodium ion battery according to the fourth aspect of the present invention has at least the following beneficial effects:

[0035] The sodium ion battery provided by the present invention has high specific capacity and capacity retention rate, good rate performance and long cycle performance, and good air stability, and can be stably placed in an air environment for 12 months without obvious attenuation of electrochemical performance.

[0036] The fifth aspect of the present invention provides an application of the sodium ion battery described in the fourth aspect of the present invention in the field of energy storage.

[0037] The application according to the fifth aspect of the present invention has at least the following beneficial effects:

[0038] The sodium ion battery provided by the present invention has good electrochemical performance and air stability, and has low preparation cost and simple preparation method, and has good application prospects in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the structure of the sodium iron sulfate material in the embodiment of the present invention.

[0040] Figure 2 The XRD patterns of the fresh sample obtained in Material Example 1 and the sample after being placed in the air for 12 months.

[0041] Figure 3 These are SEM images of a fresh sample obtained in Material Example 1 and a sample after being stored in the air for 12 months.

[0042] Figure 4These are SEM images of a fresh sample obtained from Material Comparative Example 1 and a sample after being stored in the air for 12 months.

[0043] Figure 5 The first cycle charge and discharge curves of battery Example 1 using fresh samples and samples after being stored for 12 months.

[0044] Figure 6 The cycling capacity graphs of battery Example 1 are for fresh samples and samples after 12 months of storage. DETAILED DESCRIPTION

[0045] The following is a detailed description of the embodiments of the present invention, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. The term "comprising" and other equivalent descriptions involved in the specification and claims of this application are intended to cover non-exclusive inclusions, including both the contents clearly described in the specification and claims and the steps or units that are not described in the specification and claims but are inherent in the product, method or structure.

[0046] The first aspect of the embodiment of the present invention provides a sodium iron sulfate material, the structural schematic diagram of which is as follows Figure 1 As shown, it includes a sodium iron sulfate crystalline phase, at least a portion of the surface of the sodium iron sulfate crystalline phase is covered with a sodium iron sulfate amorphous phase.

[0047] In the present invention, at least part of the surface of the sodium ferric sulfate crystalline phase is coated with a highly stable sodium ferric sulfate amorphous phase. On the one hand, the amorphous phase wraps the sodium ferric sulfate crystalline particles inside, which is conducive to isolating the sodium ferric sulfate from contact with the air, protecting the sodium ferric sulfate, and achieving the purpose of improving the air stability of the sodium ferric sulfate; on the other hand, the amorphous phase provides abundant vacancy defects, which makes metal migration (such as Na + ) becomes easier than in the crystalline phase, thereby promoting electrode kinetics. The conversion reaction can be introduced by virtue of the inherent defects in the amorphous structure, and the amorphous phase characteristics make the material less susceptible to potential structural disorders associated with repeated conversion / reconversion reactions, resulting in a sodium iron sulfate material with stable performance.

[0048] In some embodiments of the present invention, the sodium iron sulfate amorphous phase is formed by heat treating the sodium iron sulfate crystalline phase.

[0049] The sodium iron sulfate crystalline phase in the present invention can form the surface-coated sodium iron sulfate amorphous phase after heat treatment, without adding additional inactive raw materials to form a coating layer, the preparation process is simple, and the obtained sodium iron sulfate material has good air stability and excellent electrochemical performance.

[0050] A second aspect of the embodiment of the present invention provides a method for preparing the sodium iron sulfate material according to the first aspect of the embodiment of the present invention, comprising the following steps:

[0051] S1, heating the sodium iron sulfate crystals to a temperature T under a first protective gas atmosphere and a pressure P, and keeping the temperature for a time t, then stopping the heating to obtain a heat-treated sample;

[0052] S2, maintaining the pressure at P, introducing the second protective gas at a flow rate v, cooling the heat-treated sample, and obtaining the sodium iron sulfate material after cooling;

[0053] Among them, the pressure P ranges from 0.1 to 1000 MPa; the temperature T ranges from 350 to 3000°C; the time t ranges from 0.1 to 15 s; the flow rate v ranges from 50 to 2000 mL / min; the first protective gas and the second protective gas are the same or different.

[0054] The present invention conducts rapid heat treatment on sodium ferric sulfate crystals in an atmosphere of protective gas by heat treatment under specific conditions, rapidly heats up in a very short time to form an ultrafast thermal shock effect, and then rapidly cools and quenches to complete the amorphous transformation on the surface of the grains. This highly stable amorphous package isolates the contact between the internal sodium ferric sulfate particles and the air, and effectively improves the air stability of the sodium ferric sulfate material. In addition, heat treatment under high temperature conditions promotes the structural reorganization of the sodium ferric sulfate material, reduces the original defects, and further improves the structure and electrochemical properties of the sodium ferric sulfate material. The preparation method provided by the present invention has simple preparation steps, low energy consumption, and good uniformity and high yield of the obtained product. The sodium ferric sulfate material obtained by the method has good air stability, rate performance and long cycle performance. The material can be left in the air for a long time, and the electrochemical performance after being left for 12 months has no obvious decline.

[0055] In some embodiments of the present invention, in step S1, heating is instantaneous heating; in some specific embodiments of the present invention, instantaneous heating means that the time required for heating to temperature T is ≤10s; in some examples of the present invention, instantaneous heating means that the time required for heating to temperature T is ≤1s; non-limiting specific examples are 0.01 s, 0.1 s, 0.3 s or 0.5 s.

[0056] In some embodiments of the present invention, in step S1, the heating method is selected from Joule heat treatment.

[0057] In some embodiments of the present invention, the pressure P is 0.5-500 MPa; in some specific embodiments of the present invention, the pressure P is 1-200 MPa; in some examples of the present invention, the pressure P is 5-50 MPa. Non-limiting specific examples include 5 MPa, 10 MPa, 15 MPa, 20 MPa, 30 MPa, 40 MPa or 50 MPa.

[0058] In some embodiments of the present invention, the temperature T is 360-2000° C.; in some specific embodiments of the present invention, the temperature T is 380-1500° C.; in some examples of the present invention, the temperature T is 400-1000° C. Non-limiting specific examples include 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., or 1000° C.

[0059] In some embodiments of the present invention, the time t is 0.3-10 s; in some specific embodiments of the present invention, the time t is 0.4-5 s; in some examples of the present invention, the time t is 0.5-3 s. Non-limiting specific examples are 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s or 3 s.

[0060] In some embodiments of the present invention, the flow rate v is 100-1500 mL / min; in some specific embodiments of the present invention, the flow rate v is 200-1200 mL / min; in some examples of the present invention, the flow rate v is 300-1000 mL / min. Non-limiting specific examples are 300 mL / min, 400 mL / min, 500 mL / min, 600 mL / min, 700 mL / min, 800 mL / min, 900 mL / min or 1000 mL / min.

[0061] In some embodiments of the present invention, the first protective gas is the same as the second protective gas.

[0062] In some embodiments of the present invention, the first protective gas includes an inert gas, a reducing gas or a combination thereof; in some specific embodiments of the present invention, the first protective gas is selected from a reducing gas, or a combination of an inert gas and a reducing gas; in some examples of the present invention, the first protective gas is selected from a combination of an inert gas and a reducing gas.

[0063] In some embodiments of the present invention, the volume ratio of the inert gas to the reducing gas in the first protective gas is 1:(0.1-5); in some specific embodiments of the present invention, the volume ratio of the inert gas to the reducing gas in the first protective gas is 1:(0.5-3); in some examples of the present invention, the volume ratio of the inert gas to the reducing gas in the first protective gas is 1:(0.8-1.5). Non-limiting specific examples include 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5.

[0064] In some embodiments of the present invention, in the first protective gas, the inert gas includes at least one of nitrogen, argon or helium; in some specific embodiments of the present invention, in the first protective gas, the inert gas includes argon, helium or a combination thereof; in some examples of the present invention, in the first protective gas, the inert gas is selected from argon (Ar).

[0065] In some embodiments of the present invention, the reducing gas in the first protective gas includes at least one of sulfur dioxide, hydrogen or hydrogen sulfide; in some specific embodiments of the present invention, the reducing gas in the first protective gas includes sulfur dioxide, hydrogen or a combination thereof; in some examples of the present invention, the reducing gas in the first protective gas is selected from sulfur dioxide (SO2).

[0066] In some embodiments of the present invention, the first protective gas includes at least one of nitrogen, argon, helium, sulfur dioxide, hydrogen or hydrogen sulfide; in some specific embodiments of the present invention, the first protective gas includes argon, sulfur dioxide or a combination thereof; in some examples of the present invention, the first protective gas is selected from sulfur dioxide, or a combination of argon and sulfur dioxide; in some specific examples of the present invention, the first protective gas is selected from a combination of argon and sulfur dioxide.

[0067] In some embodiments of the present invention, the second protective gas includes an inert gas, a reducing gas or a combination thereof; in some specific embodiments of the present invention, the second protective gas is selected from a reducing gas, or a combination of an inert gas and a reducing gas; in some examples of the present invention, the second protective gas is selected from a combination of an inert gas and a reducing gas.

[0068] In some embodiments of the present invention, the volume ratio of the inert gas to the reducing gas in the second protective gas is 1:(0.1-5); in some specific embodiments of the present invention, the volume ratio of the inert gas to the reducing gas in the second protective gas is 1:(0.5-3); in some examples of the present invention, the volume ratio of the inert gas to the reducing gas in the second protective gas is 1:(0.8-1.5). Non-limiting specific examples include 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5.

[0069] In some embodiments of the present invention, the inert gas in the second protective gas includes at least one of nitrogen, argon or helium; in some specific embodiments of the present invention, the inert gas in the second protective gas includes argon, helium or a combination thereof; in some examples of the present invention, the inert gas in the second protective gas is selected from argon (Ar).

[0070] In some embodiments of the present invention, the reducing gas in the second protective gas includes at least one of sulfur dioxide, hydrogen or hydrogen sulfide; in some specific embodiments of the present invention, the reducing gas in the second protective gas includes sulfur dioxide, hydrogen or a combination thereof; in some examples of the present invention, the reducing gas in the second protective gas is selected from sulfur dioxide (SO2).

[0071] In some embodiments of the present invention, the second protective gas includes at least one of nitrogen, argon, helium, sulfur dioxide, hydrogen or hydrogen sulfide; in some specific embodiments of the present invention, the second protective gas includes argon, sulfur dioxide or a combination thereof; in some examples of the present invention, the second protective gas is selected from sulfur dioxide, or a combination of argon and sulfur dioxide; in some specific examples of the present invention, the second protective gas is selected from a combination of argon and sulfur dioxide.

[0072] In some embodiments of the present invention, the chemical formula of sodium iron sulfate crystals is Na 2+x Fe 2-y (SO4)3, x=0~0.7, y=0~0.35.

[0073] In some embodiments of the present invention, the raw materials for preparing sodium iron sulfate crystals include an iron source, a sodium source and a sulfur source.

[0074] In some embodiments of the present invention, the iron source includes at least one of ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous sulfate, ammonium ferrous sulfate, ammonium ferric sulfate, ferric nitrate, ferrous chloride, ferric chloride or ammonium ferric citrate; in some specific embodiments of the present invention, the iron source includes at least one of ferrous sulfate, ferrous sulfate, ammonium ferrous sulfate or ammonium ferric sulfate; in some examples of the present invention, the ferrous source is selected from ferrous sulfate.

[0075] In some embodiments of the present invention, ferrous sulfate is selected from ferrous sulfate hydrates; in some specific embodiments of the present invention, the hydrate of ferrous sulfate includes at least one of ferrous sulfate monohydrate, ferrous sulfate pentahydrate or ferrous sulfate heptahydrate.

[0076] In some embodiments of the present invention, the sodium source includes at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium citrate or sodium hydroxide; in some specific embodiments of the present invention, the sodium source includes sodium sulfate, sodium bisulfate or a combination thereof; in some examples of the present invention, the sodium source is selected from sodium sulfate.

[0077] In some embodiments of the present invention, the sulfur source includes at least one of ferrous sulfate, ferric sulfate, ammonium ferrous sulfate, ammonium ferric sulfate, sodium sulfate, sodium bisulfate, potassium sulfate or ammonium sulfate; in some specific embodiments of the present invention, the sulfur source includes at least one of ferrous sulfate, ferric sulfate, ammonium ferrous sulfate, ammonium ferric sulfate, sodium sulfate or sodium bisulfate; in some examples of the present invention, the sulfur source includes ferrous sulfate, sodium sulfate or a combination thereof.

[0078] In some embodiments of the present invention, the preparation method of sodium ferric sulfate crystals includes a solid phase method or a liquid phase method. The solid phase method is to perform high-temperature solid-phase sintering of the raw materials for preparing sodium ferric sulfate in an atmosphere of protective gas; the liquid phase method is to react the raw materials for preparing sodium ferric sulfate in a liquid phase state to prepare sodium ferric sulfate. The present invention does not specifically limit the preparation method of sodium ferric sulfate, and the preparation method of sodium ferric sulfate includes but is not limited to the solid phase method or the hydrothermal method.

[0079] A third aspect of an embodiment of the present invention provides a sodium iron sulfate positive electrode material, and the raw materials for preparing the sodium iron sulfate positive electrode material include the sodium iron sulfate material of the first aspect of the embodiment of the present invention, or the sodium iron sulfate material prepared by the preparation method of the second aspect of the embodiment of the present invention.

[0080] The sodium ferric sulfate material prepared by the preparation method of the first aspect of the embodiment of the present invention and the second aspect of the embodiment of the present invention has good air stability and can be stably placed in an air environment for 12 months without obvious attenuation of electrochemical performance; the sodium ferric sulfate material is made into a positive electrode material to obtain good electrochemical performance.

[0081] In some embodiments of the present invention, the raw materials for preparing the sodium iron sulfate positive electrode material also include a conductive agent, a binder and an organic solvent.

[0082] In some embodiments of the present invention, the conductive agent includes at least one of conductive carbon, acetylene black, carbon nanotubes or graphene; in some specific embodiments of the present invention, the conductive agent includes conductive carbon, acetylene black or a combination thereof; in some examples of the present invention, the conductive agent is selected from conductive carbon (SuperP).

[0083] In some embodiments of the present invention, the binder includes at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose, polymethyl methacrylate, styrene-butadiene rubber or polyvinyl alcohol; in some specific embodiments of the present invention, the binder includes at least one of polyvinylidene fluoride, polyacrylic acid or polyacrylonitrile; in some examples of the present invention, the binder is selected from polyvinylidene fluoride.

[0084] In some embodiments of the present invention, the organic solvent includes at least one of N,N-dimethylformamide, nitrogen methyl pyrrolidone, acetone or tetrahydrofuran; in some specific embodiments of the present invention, the organic solvent includes N,N-dimethylformamide, nitrogen methyl pyrrolidone or a combination thereof; in some examples of the present invention, the organic solvent is selected from nitrogen methyl pyrrolidone (NMP).

[0085] In some embodiments of the present invention, the mass ratio of the sodium ferric sulfate material to the conductive agent is 1: (0.01-1); in some specific embodiments of the present invention, the mass ratio of the sodium ferric sulfate material to the conductive agent is 1: (0.05-0.5); in some examples of the present invention, the mass ratio of the sodium ferric sulfate material to the conductive agent is 1: (0.1-0.3). Non-limiting specific examples include 1: 0.1, 1: 0.125, 1: 0.15, 1: 0.2, 1: 0.25 or 1: 0.3.

[0086] In some embodiments of the present invention, the mass ratio of the sodium ferric sulfate material to the binder is 1: (0.01-1); in some specific embodiments of the present invention, the mass ratio of the sodium ferric sulfate material to the binder is 1: (0.05-0.5); in some examples of the present invention, the mass ratio of the sodium ferric sulfate material to the binder is 1: (0.1-0.3). Non-limiting specific examples include 1: 0.1, 1: 0.125, 1: 0.15, 1: 0.2, 1: 0.25 or 1: 0.3.

[0087] In some embodiments of the present invention, the raw materials for preparing the sodium iron sulfate positive electrode material also include a base material.

[0088] In some embodiments of the present invention, the sodium ferric sulfate positive electrode material is prepared by a method comprising the following steps: mixing the sodium ferric sulfate material, a conductive agent, a binder and an organic solvent to obtain a conductive slurry; applying the conductive slurry on a base material and drying it to form the sodium ferric sulfate positive electrode material.

[0089] In some embodiments of the present invention, the conductive paste is applied to the base material with a thickness of 1 to 3 micrometers; non-limiting specific examples include 1 micrometer, 1.5 micrometers, 2 micrometers, 2.5 micrometers or 3 micrometers.

[0090] The fourth aspect of the embodiments of the present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material, an electrolyte and a separator; the positive electrode material is selected from the sodium iron sulfate positive electrode material of the third aspect of the embodiments of the present invention.

[0091] In some embodiments of the present invention, the negative electrode material is selected from sodium.

[0092] In some embodiments of the present invention, the electrolyte includes an electrolyte and a solvent; the electrolyte is selected from sodium salt; and the solvent includes an ester solvent, an ether solvent or a combination thereof.

[0093] In some embodiments of the present invention, the concentration of the electrolyte in the electrolyte is 0.5~2 mol / L; in some specific embodiments of the present invention, the concentration of the electrolyte in the electrolyte is 0.8~1.2 mol / L; non-limiting specific examples are 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L or 1.2 mol / L.

[0094] In some embodiments of the present invention, in the electrolyte, the sodium salt includes at least one of NaPF6, NaOTF, NaFSI, NaTFSI, NaBF4, NaBOB, NaDFOB or NaClO4; in some specific embodiments of the present invention, in the electrolyte, the sodium salt includes at least one of NaPF6, NaBF4 or NaClO4; in some examples of the present invention, in the electrolyte, the sodium salt is selected from NaClO4.

[0095] In some embodiments of the present invention, in the electrolyte, the solvent includes at least one of ethylene glycol dimethyl ether (DME), dioxolane (DOL), propylene carbonate (PC), ethylene carbonate (EC) or diethyl carbonate (DEC); in some specific embodiments of the present invention, in the electrolyte, the solvent includes at least one of propylene carbonate (PC), ethylene carbonate (EC) or diethyl carbonate (DEC); in some examples of the present invention, in the electrolyte, the solvent includes propylene carbonate (PC), ethylene carbonate (EC) or a combination thereof.

[0096] In some embodiments of the present invention, in the solvent of the electrolyte, the volume ratio of propylene carbonate (PC) to ethylene carbonate (EC) is 1:(0.5-2); non-limiting specific examples are 1:0.5, 1:1, 1:1.5 or 1:2.

[0097] A fifth aspect of the embodiments of the present invention provides an application of the sodium ion battery as described in the fourth aspect of the embodiments of the present invention in the field of energy storage.

[0098] The sodium ion battery provided in the embodiment of the present invention has good electrochemical performance and air stability, and has low preparation cost and simple preparation method, and has good application prospects in the field of energy storage.

[0099] In some embodiments of the present invention, the energy storage field includes at least one of the mobile phone field, computer field, automobile field, aircraft field or communication base station field.

[0100] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0101] Material Example 1

[0102] This example provides a sodium iron sulfate material, which is prepared by the following steps:

[0103] S1: Sodium sulfate and ferrous sulfate hydrate are used as raw materials to prepare sodium ferric sulfate (Na 2+x Fe 2-y (SO4)3, x=0~0.7, y=0~0.35);

[0104] S2: The prepared sodium iron sulfate positive electrode is placed in a closed Joule heating device, and is instantaneously heated to 800°C (T) in an atmosphere of protective gas SO2 at a pressure (P) of 10 MPa, and maintained for 1.5 s (t), and then the heating is stopped;

[0105] S3: Keep the pressure the same as step S2 (P), use a flow rate (V) of 800 mL / min, pass the same protective gas as step S2, cool the sample, and stop passing the gas when the surface temperature of the sample drops to room temperature, then reduce the pressure to normal pressure to obtain the target product.

[0106] Material Examples 2 to 68

[0107] Material Examples 2 to 68 each provide a sodium iron sulfate material, which differs from Material Example 1 in that some experimental conditions in Material Examples 2 to 68 are different, and the specific experimental conditions are: protective atmosphere in step S2, experimental pressure P, experimental heating reaction temperature (T), insulation time (t), and gas flow rate (V) in step S3. The experimental conditions of Material Examples 2 to 68 are shown in Table 1. Except for the experimental conditions in Table 1, the raw materials and other steps of Material Examples 2 to 68 are the same as those of Material Example 1.

[0108] Specifically, compared with Material Example 1, Material Examples 2 to 11 only change the value of the experimental pressure P in the description of step S2; compared with Material Example 1, Material Examples 12 to 19 only change the value of the experimental heating reaction temperature T in the description of step S2; compared with Material Example 1, Material Examples 20 to 32 only change the value of the insulation time t in the description of step S2; compared with Material Example 1, Material Examples 33 to 44 only change the value of the gas flow rate v during cooling in the description of step S3; compared with Material Example 1, Material Examples 45-61 only change the protective atmosphere in the reaction conditions; compared with Material Example 45, Material Example 62 only changes the value of the reaction temperature in the description of step S2. The value of the experimental pressure P is changed; compared with Material Example 45, Material Example 63 changes the value of the experimental pressure P described in step S2 and the value of the gas flow rate v during cooling described in step S3; Material Examples 64~65, compared with Material Example 45, change the value of the experimental heating reaction temperature T described in step S2 and the value of the gas flow rate v during cooling described in step S3; Material Example 66, compared with Material Example 45, changes the value of the insulation time t described in step S2 and the value of the gas flow rate v during cooling described in step S3; Material Examples 67~68, compared with Material Example 45, only change the value of the gas flow rate v during cooling described in step S3.

[0109] In Table 1, the volume ratio of Ar to SO2 in the "Ar+SO2" mixed gas is 1:1, and the same applies to the others. The embodiments not marked with "first" or "second" refer to the first protective gas and the second protective gas using the same gas; the embodiments marked with "first" or "second" refer to the first protective gas and the second protective gas, respectively.

[0110] Table 1 Experimental conditions of material examples 1 to 68

[0111]

[0112] Table 1

[0113]

[0114] Table 1

[0115]

[0116] Material Comparative Example 1

[0117] This example provides a sodium iron sulfate material, which is different from Material Example 1 in that the material of this example is prepared by only using the method in step S1 of Material Example 1, and steps S2 and S3 of Material Example 1 are not performed.

[0118] Material Comparative Example 2

[0119] This example provides a sodium iron sulfate material. The difference from Material Example 1 is that the material of this example is prepared under a vacuum environment, and the other specific steps are the same as those in Material Example 1.

[0120] Material Comparative Example 3

[0121] This example provides a sodium iron sulfate material, which is different from Material Example 1 in that in step S3 of this example, under the condition of maintaining the pressure P1, no protective gas is introduced, the sample is naturally cooled, and when the surface temperature of the sample drops to room temperature, the pressure is then reduced to normal pressure. The other specific steps are the same as those in Material Example 1.

[0122] Material Comparative Example 4

[0123] This example provides a sodium iron sulfate material, which is different from material example 1 in that, in step S3 of this example, without maintaining the pressure P1, a protective gas is introduced to reduce the pressure to normal pressure, and the sample is cooled until the surface temperature of the sample drops to room temperature. The other specific steps are the same as those in material example 1.

[0124] Battery Example 1

[0125] This example provides a sodium ion battery, which is prepared by using the fresh sample obtained in Material Example 1 and the sample after being left in the air for 12 months as the positive electrode active material. The preparation method comprises the following steps:

[0126] (1) Preparation of positive electrode: The positive electrode active material, conductive carbon (SuperP), and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1. After sufficient grinding, an appropriate amount of nitrogen methyl pyrrolidone is added to form a uniform slurry. The slurry is coated on the surface of aluminum foil with a scraper to a thickness of 2 μm. After vacuum drying, it is cut into discs with a diameter of 10 mm, compacted, and reserved as positive electrode sheets for later use.

[0127] (2) Preparation of negative electrode: In an inert gas-protected glove box, press metallic sodium into thin sheets, cut into 12 mm diameter discs, and reserve them for use as the negative electrode of the battery.

[0128] (3) Preparation of diaphragm: Cut the commercial glass fiber film into discs with a diameter of 16 mm and set aside as diaphragm.

[0129] (4) Battery assembly: In an inert gas-protected glove box, the prepared positive electrode, separator and negative electrode are tightly stacked in sequence, and commercial electrolyte (1.0 M NaClO4 in EC:PC = 1:1 Vol%) is added to completely soak the separator. The stacked parts are then encapsulated into a button cell casing to complete the battery assembly.

[0130] Battery Examples 2 to 68

[0131] Battery Examples 2 to 68 each provide a sodium ion battery, which differs from Battery Example 1 in that the positive electrode active materials of Battery Examples 2 to 68 respectively use the samples prepared in Material Examples 2 to 68, and the other raw materials and preparation steps are the same as those of Battery Example 1.

[0132] Battery comparison 1~4

[0133] Battery Comparative Examples 1 to 4 each provide a sodium ion battery, which differs from Battery Example 1 in that the positive electrode active materials of Battery Comparative Examples 1 to 4 are samples prepared in Material Comparative Examples 1 to 4, respectively, and other raw materials and preparation steps are the same as those of Battery Example 1.

[0134] Performance Testing

[0135] (1) Characterization of material structure and morphology.

[0136] Figure 2 The XRD diagrams of the fresh sample obtained in Material Example 1 and the sample after being placed in the air for 12 months are shown in the figure. As can be seen from the figure, the diffraction spectrum of the fresh sample obtained in Material Example 1 matches well with the standard diffraction spectrum of ferrous sulfate, and the XRD of the sample after being placed in the air for 12 months still matches well with the standard diffraction spectrum. The surface amorphous phase cannot be seen in the XRD diagram because the amorphous phase itself has no diffraction peaks and the amorphous phase content is very small.

[0137] Figure 3 The SEM images of the fresh sample obtained in Material Example 1 and the sample after being placed in the air for 12 months, wherein (A) is the fresh sample and (B) is the sample after being placed in the air for 12 months. As can be seen from the figure, the morphology of the sample obtained in Material Example 1 did not change significantly before and after being placed in the air for 12 months.

[0138] Figure 4 The SEM images of the fresh sample obtained in Material Comparative Example 1 and the sample after being placed in the air for 12 months, where (A) is the fresh sample and (B) is the sample after being placed in the air for 12 months. As can be seen from the figure, the fresh sample particles obtained in Material Comparative Example 1 without Joule heat treatment have sharp edges and a smooth surface; after being placed in the air for 12 months, the edges and corners weaken and the surface smoothness decreases, indicating that the sample has changed after being placed.

[0139] contrast Figure 3 and Figure 4 It was found that compared with material comparison example 1, the sample particles of material example 1 were more rounded after amorphization treatment, and most of them were spherical, indicating that after being treated with steps S2-S3 in the method of material example 1, the surface of the sample particles changed and was no longer in its original state.

[0140] (2) Electrochemical tests were performed on the sodium ion batteries of battery examples 1 to 68 and battery comparison examples 1 to 4. The constant current charge and discharge test was performed using the BTSDA test system of Shenzhen Xinwei Electronics Co., Ltd. The environment was a constant temperature and humidity room (25°C, 35%), and the test voltage range was 2.0-4.5 V; the first ten cycles were at a rate of 0.1C, and the rate was changed to 1C (1C=120mAh / g) from the eleventh cycle. The test results are shown in Table 2; the median voltage refers to the median voltage of the 100th cycle, and the capacity retention rate refers to the capacity retention rate of the 1000th cycle relative to the 11th cycle.

[0141] Table 2 Electrochemical test results of sodium ion batteries of battery examples 1 to 68 and battery comparative examples 1 to 4

[0142]

[0143] Table 2

[0144]

[0145] Table 2

[0146]

[0147] Table 2

[0148]

[0149] The following conclusions can be drawn from Table 2:

[0150] (I) Analysis of battery examples 1 to 68 shows that different preparation conditions have different effects on product performance, and the influence rules are summarized as follows:

[0151] (1.1) Battery Examples 2 to 11 are compared with Battery Example 1. It can be seen that the electrochemical performance and air stability of the products vary with the change of reaction pressure. The electrochemical performance and air stability of the products are optimal when the pressure is 10 MPa.

[0152] (1.2) Battery Examples 12 to 19 are compared with Battery Example 1. It can be seen that when the reaction temperature is too low, the specific capacity of the fresh sample and the sample after being shelved for 12 months is reduced, and the specific capacity after being shelved is reduced more seriously, indicating that the temperature is too low, which is not conducive to the formation of amorphous phase, and the structure cannot be reorganized to reduce the original defects. Therefore, the performance and air stability of the sample are not good; when the reaction temperature reaches a certain value, if it is not matched with the reaction pressure, the sample will decompose, which will have a negative impact on the electrochemical performance and air stability of the sample, and cause energy waste.

[0153] (1.3) Compared with Battery Example 1, Battery Examples 20 to 32 show that when the insulation time is too short, the specific capacity of the fresh sample and the sample after 12 months of storage is reduced, and the specific capacity after storage is reduced more seriously, indicating that the insulation time affects the thickness of the amorphous phase. If the time is too short, the amorphous phase is thin and cannot fully protect the internal materials. In addition, the structural reorganization is not comprehensive and defects still remain. Therefore, the performance and air stability of the sample are not good. If the insulation time is too long, the thickness of the amorphous phase is not conducive to the electrode reaction, and the sample will inevitably decompose, which has a negative impact on the electrochemical performance and air stability of the sample, and causes energy waste.

[0154] (1.4) Compared with Battery Example 1, Battery Examples 33 to 44 show that as the air flow rate increases, the electrochemical performance and air stability of the product gradually improve, indicating that simply changing the air flow rate can control the sample cooling rate and the quality of the amorphous phase, which has a positive effect on the electrochemical performance and air stability of the sample.

[0155] (1.5) Compared with battery examples 1 to 44, battery examples 45 to 61 show that the type of atmosphere has little effect on the electrochemical properties and air stability of the products.

[0156] (1.6) Compared with battery embodiments 1-61, the conclusions of battery embodiments 62-68 are consistent with those of (1.1)-(1.4). The sodium iron sulfate material and sodium ion battery prepared under the specific conditions of the present invention have good electrochemical properties and air stability.

[0157] (II) Comparison of battery examples 1 to 68 with battery comparative examples 1 to 4 shows the following conclusions:

[0158] (2.1) The comparison results of battery examples 1 to 68 and battery comparison example 1 show that when the amorphization treatment is not performed, the electrochemical performance of the initial samples is lower than that of the treated samples, and the electrochemical performance of the samples after being shelved for 12 months has significantly declined, indicating that amorphization can effectively improve the air stability and electrochemical performance of the samples.

[0159] (2.2) The comparison results of battery examples 1 to 68 with battery comparison example 2 show that when in a vacuum environment, the electrochemical performance of the samples decreases, and the electrochemical performance of the samples significantly decayed after being left for 12 months, but the capacity retention rate is slightly better than that of battery comparison example 1. It is speculated that the possible reason is that the samples decompose at a faster rate under high temperature vacuum conditions, forming an inactive phase, which causes the electrochemical performance to decrease. The inactive phase cannot effectively prevent the internal materials from being affected by environmental factors, so the electrochemical performance significantly decays.

[0160] (2.3) The comparison results of battery examples 1 to 68 and battery comparison example 3 show that the rapid flow of protective atmosphere can effectively and quickly reduce the sample temperature and improve the air stability of the sample. It is speculated that the possible reason is that when the sample is naturally cooled, the slow cooling rate is not conducive to the formation of amorphous phase, and the amorphous phase cannot be wrapped and the internal material is not formed, so the air stability of the sample is poor.

[0161] (2.4) The comparison results of battery examples 1 to 68 and battery comparative example 4 show that when the pressure is not maintained and the protective gas is directly introduced to reduce the pressure to normal pressure and the sample is cooled, the electrochemical performance of the sample is reduced. It is speculated that the possible reason is that the sample decomposes during the cooling process to form an inactive phase, which has a negative impact on the electrochemical performance and air stability of the sample.

[0162] Figure 5 The first cycle charge and discharge curves of the fresh sample and the sample after being stored for 12 months of battery Example 1; Figure 6 The cycle capacity diagram of the fresh sample and the sample after 12 months of storage for battery example 1 is shown in FIG. Figures 5 and 6 It can be seen that the first cycle charge and discharge curves of the fresh sample of battery embodiment 1 and the sample after being shelved for 12 months are basically consistent; the capacity retention rate of the fresh sample after 1000 cycles is 87.6%, and the capacity retention rate of the sample after being stored for 12 months is 87.5% after 1000 cycles; it can be seen that the electrochemical properties of the fresh sample of battery embodiment 1 and the sample after being shelved for 12 months are not much different, and it has good air stability.

[0163] In the embodiment of the present invention, the freshly prepared sodium ferric sulfate material is subjected to a rapid Joule heat treatment under a protective atmosphere, the temperature is rapidly raised in a very short time to form an ultrafast thermal shock effect, and then the temperature is rapidly lowered (rapid flow of protective atmosphere and rapid cooling, liquid nitrogen gas pouring, etc.) to achieve high-temperature quenching, and the surface of the sodium ferric sulfate is instantly transformed into an amorphous state, forming an air-stable amorphous phase-wrapped sodium ferric sulfate positive electrode material with a complete internal structure. On the one hand, the amorphous phase wraps the internal sodium ferric sulfate particles, isolating the contact with the air, protecting the sodium ferric sulfate, and achieving the purpose of improving the air stability of the sodium ferric sulfate; on the other hand, the amorphous phase provides abundant vacancy defects, which makes the metal migration (Na + ) becomes easier than in the crystalline phase, promoting electrode kinetics. The conversion reaction can be introduced by virtue of the amorphous structure with inherent defects, and the amorphous phase characteristics make the material less susceptible to the potential structural disorder associated with repeated conversion / reconversion reactions. In addition, the structural reorganization of the target material will be achieved under high temperature conditions, reducing the original defects and further improving the structure of sodium iron sulfate.

[0164] The surface amorphized sodium iron sulfate cathode material obtained in the embodiment of the present invention has improved cycle stability and better electrochemical performance. Compared with the existing preparation method of sodium iron sulfate material, the solution provided by the present invention has a simple process, low energy consumption, and no additional inactive components; the prepared sodium iron sulfate cathode material has good air stability, good rate performance, good long cycle performance, and good product uniformity and high yield.

[0165] In summary, the present invention coats a highly stable sodium iron sulfate amorphous phase on at least part of the surface of the sodium iron sulfate crystalline phase, effectively isolating the contact between the internal sodium iron sulfate crystalline phase particles and the air, and improving the air stability of the sodium iron sulfate material; and the amorphous amorphous phase provides abundant vacancy defects, making metal migration easier than in the crystalline phase, thereby promoting electrode kinetics. The sodium iron sulfate material provided by the present invention has good air stability, rate performance and long cycle performance. The material can be left in the air for a long time, and the electrochemical performance after being left for 12 months has no obvious decline. The material can be used to prepare a high-performance sodium ion battery.

Claims

1. A sodium iron sulfate material, characterized in that It comprises a sodium iron sulfate crystalline phase, at least a portion of the surface of the sodium iron sulfate crystalline phase is coated with a sodium iron sulfate amorphous phase; The sodium iron sulfate amorphous phase is formed by heat treating the sodium iron sulfate crystalline phase; The sodium iron sulfate material is prepared by a preparation method comprising the following steps: S1, heating the sodium iron sulfate crystals to a temperature T under a first protective gas atmosphere and a pressure P, and keeping the temperature for a time t, then stopping the heating to obtain a heat-treated sample; S2, maintaining the pressure at P, introducing a second protective gas at a flow rate v, cooling the heat-treated sample, and obtaining the sodium iron sulfate material after cooling; The pressure P is in the range of 0.1-1000 MPa; the temperature T is in the range of 350-3000°C; the time t is in the range of 0.1-15 s; the flow rate v is in the range of 50-2000 mL / min; the first protective gas is the same as or different from the second protective gas; The chemical formula of the sodium iron sulfate crystal is Na 2+x Fe 2-y (SO4)3, x=0~0.7, y=0~0.

35.

2. A method for preparing the sodium iron sulfate material according to claim 1, characterized in that: The following steps are involved: S1, heating the sodium iron sulfate crystals to a temperature T under a first protective gas atmosphere and a pressure P, and keeping the temperature for a time t, then stopping the heating to obtain a heat-treated sample; S2, maintaining the pressure at P, introducing a second protective gas at a flow rate v, cooling the heat-treated sample, and obtaining the sodium iron sulfate material after cooling; The pressure P is in the range of 0.1-1000 MPa; the temperature T is in the range of 350-3000°C; the time t is in the range of 0.1-15 s; the flow rate v is in the range of 50-2000 mL / min; the first protective gas is the same as or different from the second protective gas; The chemical formula of the sodium iron sulfate crystal is Na 2+x Fe 2-y (SO4)3, x=0~0.7, y=0~0.

35.

3. The preparation method according to claim 2, characterized in that: The first protective gas includes an inert gas, nitrogen, a reducing gas or a combination thereof; and / or the second protective gas includes an inert gas, nitrogen, a reducing gas or a combination thereof.

4. The preparation method according to claim 3, characterized in that: The first protective gas includes at least one of nitrogen, argon, helium, sulfur dioxide, hydrogen or hydrogen sulfide; and / or the second protective gas includes at least one of nitrogen, argon, helium, sulfur dioxide, hydrogen or hydrogen sulfide.

5. The preparation method according to claim 2, characterized in that: The raw materials for preparing the sodium ferric sulfate crystals include an iron source, a sodium source and a sulfur source.

6. The preparation method according to claim 5, characterized in that: The iron source comprises at least one of ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous sulfate, ammonium ferrous sulfate, ammonium ferric sulfate, ferric nitrate, ferrous chloride, ferric chloride or ammonium ferric citrate; and / or, the sodium source comprises at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium citrate or sodium hydroxide; And / or, the sulfur source includes at least one of ferrous sulfate, ferric sulfate, ammonium ferrous sulfate, ammonium ferric sulfate, sodium sulfate, sodium bisulfate, potassium sulfate or ammonium sulfate.

7. A sodium iron sulfate positive electrode material, characterized in that: The raw material for preparing the sodium ferric sulfate positive electrode material includes the sodium ferric sulfate material according to claim 1, or the sodium ferric sulfate material prepared by the preparation method according to any one of claims 2 to 6.

8. A sodium ion battery, characterized in that: It comprises a positive electrode material, a negative electrode material, an electrolyte and a separator; the positive electrode material is selected from the sodium iron sulfate positive electrode material described in claim 7.

9. Use of the sodium ion battery as claimed in claim 8 in the field of energy storage.

Citation Information

Patent Citations

  • Positive electrode material and preparation method and application thereof

    CN118658993A

  • IN102011110003758